Comment on Balàka et al. Updated Checklist of Chondrichthyan Species in Croatia (Central Mediterranean Sea). Biology 2023, 12, 952 - Alen Soldo; Lovrenc Lipej (Biology, 2024)
The authors write that the last checklist for Croatia was carried out in 2009 and that 52 chondrichthyan species were reported in Croatian waters [...]